The Mobile Paradox: Examining Smartphone Addiction's Influence on Adolescent Health and Aggression (Medical Forum Monthly, 2023)
Objective: The objective of this study was to determine the relationship between Smartphone Addiction on Adolescent Health and Aggression Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the Institute of Professional Psychology including Bahria University, Karachi from August 2022 to January 2023. Materials and Methods: This study was conducted using a purposive sampling method on 254 participants (127 women and 127 men) aged 10 to 21. The data collection tool includes a demographic questionnaire, a screening questionnaire, a smartphone dependence questionnaire, an aggression questionnaire (AQ) and a physical health questionnaire (PHQ-9). Data were analyzed by SPSS with the Pearson correlation for relationship between variables. Results: The correlation between the dependence of smartphones (SD) and aggression (AQ) was significant, with a correlation coefficient of 0.518 (p <0.001). In addition, there was a significant negative correlation between smartphone dependency (SD) and physical health (PHQ), with a correlation coefficient of -0.171 (p = 0.006). On the other hand, the correlation between aggression (AQ) and physical health (PHQ) was weak and statistically nonsignificant, with a correlation coefficient of - 0.121 (p = 0.055). Although the relationship was not significant, the negative correlation coefficient indicates that higher levels of aggression may be associated with a slight decline in physical health. Conclusion: In conclusion, overall these findings highlight the potential impact of smartphone dependence on aggression and physical health. However, further research is needed to better understand the complex relationship between these variables and explore potential underlying factors.